L’habitat et les sépultures du haut Moyen Âge (vie-ixe siècle) de Soulages (Saint-Maurice-Navacelles, Hérault) - Agnès Bergeret; Guergana Guionova; Richard Donati; Vivien Vassal; Isabel Figueiral; Vianney Forest; Laurent Bruxelles; Frédéric Chandevau; Yves Manniez; Isabelle Commandré; Bernard Gratuze; Frédéric Raynaud (Archéologie Médiévale)
Located on the plateau of Larzac, the site of Soulages testify, for the first time in this area of medium mountains, a rural settlement which developed from the 6th to the 9th century. The remains are organised in a space that groups together all the places where people lived, mixed with the burials of the inhabitants. Within this space, the buildings are divided by function: the service buildings are gathered in areas surrounded by a palisade, the main house is secluded in height. In addition to the situation of the buildings, the analysis of the construction techniques and materials also makes it possible to distinguish the main dwelling house from the functionnal buildings, with the use of stone for the former and the use of wooden load-bearing structures and earthen walls mainly for the latter. Among burials, young children are over-represented. This kind of settlement yields few material remains documenting the life of a community settled ex nihilo.